Factors Related To Maternal Readiness To Face Menopause In Lahusa Village, Lahusa District, South Nias Regency In 2020 - Agustianny Situmeang; Tinawati Nainggolan; Sifra Tobing (Institute of Computer Science (IOCS), 2020)
Menopause is a period of scientific cessation of menstruation. One of the problems in menopause will be caused by the lack of readiness of the mother in facing menopause so that it can cause the emergence of symptoms, diseases and psychological disorders that really need attention. This type of research is descriptive analytical The results of this study showed that based on the age of the majority of 40-44 years 20 people (52.63%) and based on the education of the majority of junior high schools and below 21 people (55.26%) and based on knowledge that lacked knowledge 28 people (73.68%) and based on the economy 26 people (68.42%). And this shows that probality (0.000) < α (0.05) Ho rejected means Ha accepted, it can be concluded that age, education, knowledge and economy are related to the mother's readiness in the face of menopause. It is hoped that all menopausal mothers in Lahusa village, Lahusa District, South Nias Regency in 2020 to increase higher readiness for menopause and increase higher knowledge of menopause and increase awareness and willingness to overcome disorders and readiness in menopause so as to create maternal health in facing menopause until old age.